Introduction to Business Economics - Old John; Shafto Tony (Stanley Thornes (Publishers) Ltd, 1992)
Ideal for the business studies student who wishes to gain a thorough grounding in economics. Preface, An Economic Framework, Entrepreneurship and the Structure of Business, Business Objectives, Business Growth, The Firm and the Market, Pricing in Practice, The Investment Decision, The Firm and Financial Markets, The Firm and the Public, Competition and Consumer Protection and Public Policy, Business Location and the Community, The State as Producer, The Business Firm and National Economic Policies, Business and the Changing World, Index.